Application of multidisciplinary teamwork model of continuous care in patients with psoriasis vulgaris - Xuemei CHEN; Huiyun LIU; Xiaoyu QIU; Yu WANG; Jiao ZHANG; Junfang XU (Pifu-xingbing zhenliaoxue zazhi, 2022)
Objective To explore the effect of the nurse-led multidisciplinary team (MDT) model of continuous care in patients with psoriasis vulgaris. Methods From December 2019 to December 2020,96 inpatients with psoriasis vulgaris at our hospital were randomly divided into the observation and the control groups, 48 patients per group. Following the discharge, the patients in the control group were given the traditional nurse-led continuous care, while the patients in the observation group were given multi-disciplinary team (MDT) model of continuous care, i.e. with the participation of pharmacists and clinicians. Patients in both groups were followed up for 6 months after discharge. Results The 6-month follow-up showed that patients in the observation group had lower PASI scores (3.87±1.82 vs 6.43±2.57, t=7.87, P<0.01), lower relapse rates (10.42% vs 33.33%, χ2=7.38, P=0.007), higher medication compliance (83.33% vs 16.67%, χ2=42.67, P<0.05), better knowledge of the disease (55.13±4.50 vs 47.27±4.37, t=8.68, P<0.01) and better quality of life than patients in the control group (7.67±3.52 vs 10.11±4.21, t=3.08, P=0.003). Conclusions The multidisciplinary teamwork model of continuous care can effectively reduce the area of involved skin and the recurrence rate of the disease in patients with psoriasis vulgaris, in addition to the improvements in patients' medication compliance, knowledge of the disease, as well as patients' quality of life. It is worth to try in the clinical care of psoriatic patients.